Management Required Green Space in Industrial Parks to Controlled Generated Carbon Dioxide by Existing Industries (Case study: Salimi Industrial Park) - Dariush Khodadad Lashkari; Sina Fard Moradi Nia (رویکردهای نوین در مهندسی عمران, 2018)
Nowadays, the phenomenon of global warming due to the emission of greenhouse gases by mankind is seen as an important environmental concern that endangers future prosperity. Carbon dioxide gas has the greatest impact on the global warming phenomenon among greenhouse gases in the atmosphere. Increasing greenhouse gas emissions, including carbon dioxide, results in global warming, rising sea levels and occurrence of biologic changes in the environment, subsequently it leads to the damage to plants, animals and ecosystems. In the present study, the approximate amount of carbon dioxide generated by industries in the industrial town was estimated, and then the amount of green space needed for its control and management is calculated, so in this regard, the information of 39 industrial units from different types of production is compiled and then analyzed. Based on the calculations, the approximate amount of CO2 generation in the region was 2105738 kg per day or 768594 tons per year. To absorb and control this amount of CO2 around 35 million trees per year and 23333 hectares of arable land are required. Based on the obtained values, complete management of generated carbon dioxide by green space and tree planting in that area is impossible. It should be noted that these values are calculated for all industrial units of the town in active mode, considering the closure of some of the industrial units, the actual amount will certainly be less than the calculated value.